Formal Specification Language for Vehicular Ad-Hoc Networks - Kamal Abbas, Maythem Kamal Abbas (2009)
Vehicular Ad-Hoc Network (VANET) is a form of Mobile Ad-Hoc Network (wireless Network), originally used to provide safety & comfort for passengers, & currently being used to establish Dedicated Short Range Communications (DSRC) among near by Vehicles (V2V Communications) and between vehicles and nearby fixed infrastructure equipments; Roadside equipments (V2I Communications). VANET was used also to warn drivers of collision possibilities, road sign alarms, auto-payment at road tolls and parks. Usually VANET can be found in Intelligent Transportation Systems (ITS). VANET is the current and near future hot topic for research, that has been targeted by many researchers to develop some applications and protocols specifically for the VANET. But a problem facing all VANET researchers is the unavailability of a formal specification language to specify the VANET systems, protocols, applications and scenarios proposed by those researchers. A specification language is a formal language that is used during the systems design, analysis, and requirements analysis. Using a formal specification language, a researcher can show “What his system does”, Not How. As a contribution of our research we have created a formal specification language for VANET. We made the use of some Romans characters & some basic symbols to represent VANET Systems & Applications. In addition, we have created some combined symbols to represent actions and operations of the VANET system and its participating devices. Our formal specification language covers many of the VANET aspects, and offers Validity Test and Consistency Test for the systems. Using our specification language, we have presented three different case studies based on a VANET system model we have created and put them into the system validity and consistency tests and showed how to describe a VANET system and its applications using our formal specification language.